2014
DOI: 10.1136/bmj.g2621
|View full text |Cite
|
Sign up to set email alerts
|

PLAB and UK graduates' performance on MRCP(UK) and MRCGP examinations: data linkage study

Abstract: Objectives To assess whether international medical graduates passing the two examinations set by the Professional and Linguistic Assessments Board (PLAB1 and PLAB2) of the General Medical Council (GMC) are equivalent to UK graduates at the end of the first foundation year of medical training (F1), as the GMC requires, and if not, to assess what changes in the PLAB pass marks might produce equivalence. Main outcome measures Performance at MRCP(UK) Part 1, Part 2, and PACES assessments, and MRCGP AKT and CSA ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 32 publications
4
55
1
Order By: Relevance
“…These effects seemed independent of the other variables. Previously, it has been shown that performance at both the IELTS English language test and PLAB exams predicts later achievement in postgraduate medical training in international medical graduates [11, 12]. Likewise, we found that aspects of performance on the PLAB test was predictive of both the likelihood of referral and eventual censure.…”
Section: Discussionsupporting
confidence: 68%
“…These effects seemed independent of the other variables. Previously, it has been shown that performance at both the IELTS English language test and PLAB exams predicts later achievement in postgraduate medical training in international medical graduates [11, 12]. Likewise, we found that aspects of performance on the PLAB test was predictive of both the likelihood of referral and eventual censure.…”
Section: Discussionsupporting
confidence: 68%
“…Poorer performance of IMGs in postgraduate examinations in the UK has been reported in numerous studies when compared to UK graduates [17, 18]. We also know that IMGs are more likely to be complained about to the GMC and receive more severe disciplinary action than other doctors in Fitness to Practise investigations [19, 20].…”
Section: Introductionmentioning
confidence: 91%
“…Board (PLAB) exam before applying for GP specialty training. Two recent studies looking at the predictive validity of the PLAB exam in relation to MRCP and the MRCGP outcomes, 3 and Annual Review of Competence Progression outcomes in a variety of medical specialties 5 have concluded that the current standard of PLAB is set too low, and is below the competency level expected for a UK graduate completing foundation Year 1 training. Doctors who are not equivalent at entry to GP specialty training are likely to struggle with the MRCGP unless they receive training that addresses their specific needs.…”
Section: Licensing Exams and Judicial Reviewmentioning
confidence: 99%
“…Those differentials also exist in other postgraduate and undergraduate examinations. 2,3 In the light of these differential pass rates a judicial review of the RCGP and the GMC was requested by the British Association of Physicians of Indian Origin (BAPIO). The basis for the review were three claims: that the RCGP and GMC did not comply with their public sector equality duty (PSED), that the CSA directly discriminates against IMG and BME candidates, and that the CSA indirectly discriminates against IMG and BME candidates.…”
mentioning
confidence: 99%